Interplay of PMK No. 15/2025, Trust in Government, and Tax Literacy on Tax Compliance with Digital Services as a Moderator - Aminah, Sitti (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the effect of PMK No. 15/2025, Trust in Government, and Tax Literacy on Tax Compliance, with Digital Services as a moderating variable. Data were collected from 100 individual and corporate taxpayers registered at KPP Pratama Cimahi, selected using the Slovin formula with a 10% margin of error. Most respondents belong to the Gen Z age group (17–25 years), representing a generation highly familiar with technology and digital platforms, making them relevant to the study’s focus on digital transformation in taxation. Using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach, the study analyzes direct and moderating relationships to assess the model’s explanatory power. The results show that PMK No. 15/2025 and Tax Literacy have a strong positive impact on Tax Compliance, while Trust in Government has a negative but significant effect. Digital Services significantly moderate the relationship between PMK No. 15/2025 and Tax Compliance but fail to strengthen the effects of Trust in Government and Tax Literacy. These findings indicate that digital transformation enhances regulatory effectiveness and promotes compliance, especially among digitally literate Gen Z taxpayers. However, the moderating role of digitalization remains limited when trust and literacy are not effectively aligned with the usability of the tax system